Bispecific antibodies targeting CD40 and tumor-associated antigens promote cross-priming of T cells resulting in an antitumor response superior to monospecific antibodies - Malin Lindstedt; Peter Ellmark; Lennart Greiff; Karin Hägerbrand; Laura von Schantz; Mia Thagesson; Doreen Werchau; Kristine Smedenfors; Anna Rosén; Anette Sundstedt; Adnan Deronic; Lill Ljung; et al. (Journal for ImmunoTherapy of Cancer, 2022)
Background Indications with poor T-cell infiltration or deficiencies in T-cell priming and associated unresponsiveness to established immunotherapies represent an unmet medical need in oncology. CD40-targeting therapies designed to enhance antigen presentation, generate new tumor-specific T cells, and activate tumor-infiltrating myeloid cells to remodel the tumor microenvironment, represent a promising opportunity to meet this need. In this study, we present the first in vivo data supporting a role for tumor-associated antigen (TAA)-mediated uptake and cross-presentation of tumor antigens to enhance tumor-specific T-cell priming using CD40×TAA bispecific antibodies, a concept we named Neo-X-Prime.Methods Bispecific antibodies targeting CD40 and either of two cell-surface expressed TAA, carcinoembryonic antigen-related cell adhesion molecule 5 (CEA) or epithelial cell adhesion molecule (EpCAM), were developed in a tetravalent format. TAA-conditional CD40 agonism, activation of tumor-infiltrating immune cells, antitumor efficacy and the role of delivery of tumor-derived material such as extracellular vesicles, tumor debris and exosomes by the CD40×TAA bispecific antibodies were demonstrated in vitro using primary human and murine cells and in vivo using human CD40 transgenic mice with different tumor models.Results The results showed that the CD40×TAA bispecific antibodies induced TAA-conditional CD40 activation both in vitro and in vivo. Further, it was demonstrated in vitro that they induced clustering of tumor debris and CD40-expressing cells in a dose-dependent manner and superior T-cell priming when added to dendritic cells (DC), ovalbumin (OVA)-specific T cells and OVA-containing tumor debris or exosomes. The antitumor activity of the Neo-X-Prime bispecific antibodies was demonstrated to be significantly superior to the monospecific CD40 antibody, and the resulting T-cell dependent antitumor immunity was directed to tumor antigens other than the TAA used for targeting (EpCAM).Conclusions The data presented herein support the hypothesis that CD40×TAA bispecific antibodies can engage tumor-derived vesicles containing tumor neoantigens to myeloid cells such as DCs resulting in an improved DC-mediated cross-priming of tumor-specific CD8+ T cells. Thus, this principle may offer therapeutics strategies to enhance tumor-specific T-cell immunity and associated clinical benefit in indications characterized by poor T-cell infiltration or deficiencies in T-cell priming.